2020
DOI: 10.1038/s41598-020-72609-z
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol abrogates human norovirus infectivity in a pH-dependent manner

Abstract: Alcohol-based disinfectants are widely used for the sanitization of microorganisms, especially those that cause infectious diseases, including viruses. However, since the germicidal mechanism of alcohol is lipolysis, alcohol-based disinfectants appear to have a minimal effect on non-enveloped viruses, such as noroviruses. Because there is no cultivation method for human norovirus (HuNoV) in vitro, murine norovirus and feline calicivirus have been used as surrogates for HuNoV to analyze the efficacy of disinfec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 21 publications
(37 reference statements)
1
28
0
Order By: Relevance
“…This finding indicates that simple RT-qPCR might underestimate the potential of disinfectants to inactivate HuNoV. Recently, an in vitro method for HuNoV propagation employing human intestinal organoids has been developed [23] and introduced to evaluate the inactivation capability of several disinfectants on HuNoV [22,24]. Although this method is still challenging and not standardized to compare the decontamination efficiency of disinfectants on HuNoV, a propagation assay using human intestinal organoids will help to understand the mechanism of CA to inactivate HuNoV.…”
Section: Discussionmentioning
confidence: 99%
“…This finding indicates that simple RT-qPCR might underestimate the potential of disinfectants to inactivate HuNoV. Recently, an in vitro method for HuNoV propagation employing human intestinal organoids has been developed [23] and introduced to evaluate the inactivation capability of several disinfectants on HuNoV [22,24]. Although this method is still challenging and not standardized to compare the decontamination efficiency of disinfectants on HuNoV, a propagation assay using human intestinal organoids will help to understand the mechanism of CA to inactivate HuNoV.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that alcohol has a minimal virucidal effect and that sodium hypochlorite is effective for disinfecting these nonenveloped viruses. Sato et al reported that low-pH alcohol (acid-alcohol) had virucidal efficacy against human norovirus, indicating enhancement of the virucidal effect of alcohol by acidification 24 . On the other hand, enteroviruses are well recognized to be stable under acidic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol-mediated lysis of the viral envelope that leads to the release of the internal content is shown in Figure 2. In addition, there are plausible mechanisms of alcohol as virucidal including pH-dependent inactivation, divalent metal ions, and oxidative stress for non-enveloped viruses [57][58][59]. It is worth mentioning that a study reported a greater amplification in virucidal activity against the enveloped coronaviruses with 75% isopropanol compared to the 85% ethanol-based formulation [60].…”
Section: Effects Of Different Alcohols On Coronavirus Familymentioning
confidence: 99%